Cadmium Disrupts the Balance between Hydrogen Peroxide and Superoxide Radical by Regulating Endogenous Hydrogen Sulfide in the Root Tip of Brassica rapa - Lv, Wenjing; Yang, Lifei; Xu, Cunfa; Shi, Zhiqi; Shao, Jinsong; Xian, Ming; Chen, Jian (Frontiers in Plant Science, 2017)
Cd (cadmium) stress always alters the homeostasis of ROS (reactive oxygen species) including H2O2 (hydrogen sulfide) and O2•¯ (superoxide radical), leading to the oxidative injury and growth inhibition in plants. In addition to triggering oxidative injury, ROS has been suggested as important regulators modulating root elongation. However, whether and how Cd stress induces the inhibition of root elongation by differentially regulating endogenous H2O2 and O2•¯, rather than by inducing oxidative injury, remains elusive. To address these gaps, histochemical, physiological, and biochemical approaches were applied to investigate the mechanism for Cd to fine-tune the balance between H2O2 and O2•¯ in the root tip of Brassica rapa. Treatment with Cd at 4 and 16 μM significantly inhibited root elongation, while only 16 μM but not 4 μM of Cd induced oxidative injury and cell death in root tip. Fluorescent and pharmaceutical test suggested that H2O2 and O2•¯ played negative and positive roles, respectively, in the regulation of root elongation in the presence of Cd (4 μM) or not. Treatment with Cd at 4 μM led to the increase in H2O2 and the decrease in O2•¯ in root tip, which may be attributed to the up-regulation of Br_UPB1s and the down-regulation of their predicted targets (four peroxidase genes). Cd at 4 μM resulted in the increase in endogenous H2S in root tip by inducing the up-regulation of LCDs and DCDs. Treatment with H2S biosynthesis inhibitor or H2S scavenger significantly blocked Cd (4 μM)-induced increase in endogenous H2S level, coinciding with the recovery of root elongation, the altered balance between H2O2 and O2•¯, and the expression of Br_UPB1s and two peroxidase genes. Taken together, it can be proposed that endogenous H2S mediated the phytotoxicity of Cd at low concentration by regulating Br_UPB1s-modulated balance between H2O2 and O2•¯ in root tip. Such findings shed new light on the regulatory role of endogenous H2S in plant adaptions to Cd stress.